The Prevalence of alpha-Thalassemia in Anemic US Veterans without Nutritional Deficiency or Abnormal Hemoglobin HPLC Pattern - Guerrero, MD, Jessenia; Cai, Oliver; Ahmed, MD, Shahida; Cai, MD, PhD, Donghong (North American Journal of Medicine and Science, 2017)
Alpha-thalassemia is one of the most common hemoglobin genetic abnormalities. The primary defect is the reduced or absent production of the alpha globin chains, which underlines 4 clinical conditions: 1) alpha+-thalassemia (loss of one alpha globin), 2) alpha0-thalassemia (loss of 2 alpha globins), 3) HbH disease (loss of 3 alpha globins), and 4) Hb Bart hydrops fetalis syndrome (loss of all alpha globins). Among the anemic US veteran patients, one subpopulation defies extensive workup and remains etiology unknown (normal status of iron, VitB12, and Folate, normal hemoglobin HPLC pattern, etc.). Here we present the data of alpha-thalassemia DNA analysis in this subpopulation. 156 patients were analyzed of the alpha-globin gene locus by multiplex ligation-dependent probe amplification (LabCorp, RTP, NC). The prevalence of alpha0-thalassemia was 5%, alpha+-thalassemia 26%, and negative 69%. We believe alpha-thalassemia DNA analysis might be a useful test choice in mild anemic patients with uncertain etiology. [N A J Med Sci. 2017;10(1):1-4. DOI: 10.7156/najms.2017.1001001]